Mariagrius og Brunellus : Et nyfundet latinsk digt - Schrøder, Urban (Kirkehistoriske Samlinger, 1988)
In an old folio which belonged in 1571 to the respected clergyman and author, Pastor Anders Jensen Mariager (died 1582), there is a hitherto unknown Latin poem of twenty lines, quoted in the present article. An analysis of the poem reveals that it is by Mariager and addressed to one Olaus »Brunellus«, newly returned to the parishes of Durup and Tøndering in Jutland to take up a benefice. It has been possible to draw up an otherwise missing list of priests for these parishes, and this seems to suggest that »Brunellus« is diminutive for »Brun«, and that the poem was written to Pastor Olav Brun, upon his return home to act as curate in the annexed parish for an older brother, probably sometime between 1565 and 1568. The folio, which is in the possession of the present writer, is number 22 of the folios in Pastor Manager’s library; it contains two treatises by the Calvinist theologian, Heinrich Bullinger, and two by the Lutheran Johann Brenz. Several of the folios have been annotated and underlined by Mariager.